Purity or danger? The establishment of sex trafficking as a social problem in Sweden - Heber, Anita (European journal of criminology, 2020)
Sex trafficking has become established as one of the most significant (crime) problems in the Western world. This article provides a greater understanding of how the work of certain actors, that is claims-makers, established sex trafficking as a prominent problem on the political and media agendas in Sweden during the 2000s. It can help us understand how certain crimes can achieve the position of social problems. The study analyses political texts and debates, newspaper articles and reports published by the Swedish police. The sex-trafficking discourses that were particularly dominant in the material were: ‘The ideal sex slave Lilya’ (referring to the film Lilya 4-ever), ‘The foreign threat from the East’ and ‘Hidden but well-established organized crime’. By defining sex trafficking as an important problem, with the aid of these three discourses, a large number of claims-makers were given the opportunity to emphasize threatening and racialized discourses about ‘sex slaves’, immigration and organized crime. These discourses on sex trafficking create moral borders between innocence and guilt, between belonging and unbelonging, and between purity and danger.